Label-free colorimetric estimation of proteins using nanoparticles of silver - Shrivastava, Siddhartha; Dash, Debabrata (Nano-Micro Letters, 2010)
Metallic nanoparticles have received considerable attention in bioassays and diagnostics due to their unique surface plasmon resonance (SPR) properties. Gold nanoparticles have been employed for the development of SPR-based colorimetric bioassays. In the present report we have described a sensitive colorimetric approach for estimation of proteins, within a detection limit of 10∼80 μg/mL, using unmodified silver nanoparticles. Besides the common advantages of colorimetric assay such as simplicity, high sensitivity, and low cost, our method has a label-free design and provides an important and attractive alternative to classical sensing probes and systems. The present work will contribute to the development of nanotechnology-based diagnostic tools.